Design, synthesis, and evaluation of a water soluble C5-monoketone type curcumin analogue as a potent amyloid β aggregation inhibitor. Issue 16 (15th August 2019) - Hotsumi, Mayumi; Tajiri, Misato; Nikaido, Yuri; Sato, Taki; Makabe, Koki; Konno, Hiroyuki
Graphical abstract: Highlights: AY1319 exhibits potent A β aggregation inhibition and ideal water solubility. AY1319 binds hydrophilic sites of Aβ fibrils, leading them to disaggregate into nanorod-like fragments. The cytotoxicity of AY1319 was found to be similar to that of natural CUR. Abstract: A structure activity relationship study of curcumin analogues for the inhibition of amyloid β aggregation is described. Optimization of the o -phenol and olefin spacer resulted in the identification of the C5-monoketone type curcumin analogue AY1319, which exhibited potent anti-amyloid β aggregation activity (leading to nanorod-like fragments), sufficient water solubility, and low cytotoxicity.